The Relationship Between Parenting Styles and Peer Attachment in Adolescents at X Senior High School - Saputri, Farah Septa Dhiya’ulhaq; Anggara, Onny Fransinata (Journal Research of Social Science, Economics, and Management, 2026)
Adolescence is a critical developmental period where individuals begin to build more complex social relationships outside the family. Parenting styles are believed to play a crucial role in shaping adolescents' ability to form attachments with peers, which in turn affects their emotional and social well-being. This research aims to determine the relationship between parenting styles and peer attachment among adolescents at High School X. This study uses a quantitative approach with a correlational design and survey method. The research subjects were high school students at High School X who were selected according to the research criteria, with instruments in the form of a parenting style scale and a peer attachment scale. Data analysis was conducted using a Kolmogorov-Smirnov normality test and Pearson and Spearman correlation tests. The results showed a positive and significant relationship between parenting styles and peer attachment (; ), although the strength of the relationship was relatively low. These findings indicate that parenting styles play a role in shaping adolescents' attachment to their peers, but they are not the only factor that influences the quality of adolescents' social relationships